(untitled) (Research, Society and Development, 2021)
Objective: To analyze critically and comparatively, through indicators, the clinical and care profile of patients admitted to the General Intensive Care Units and COVID of a University Hospital in Sergipe. Methods: Epidemiological, observational and longitudinal study, developed in the year 2020. Clinical and care data were collected daily, during the established hospitalization period, from which the quality indicators were composed. A statistical analysis was performed using Student’s t and Chi-square tests, considering a level of significance, p <0.05. Results: The sample consisted of 145 patients. The main cause of hospitalization in the ICU Covid was diseases of the respiratory system, 64.2%, and in the General ICU surgical conditions, 42.0%. Death rate, NIV use rate, IMV use rate and extubation failure rate showed statistically significant difference with p <0.05 when compared between groups, all of which are higher in the ICU Covid. Conclusion: Patients admitted to the Covid unit had worse outcomes in part of the ventilatory indicators as well as mortality when compared with the General ICU group. More studies are needed with themes related to indicators, quality assessment, planning and control of services in the field of Physiotherapy.